STUDI IN SILICO PREDIKSI TOKSISITAS DAN AKTIFITAS SENYAWA XANTHOANGELOL SEBAGAI INHIBISI ENZYM TIROSINASE - Dewantoro, Agung; Wilapangga, Anjas (Edu Masda Journal, 2023)
The tyrosinase enzyme plays an important role in the synthesis of melanin, which caused the process of skin hyperpigmentation. One of the main chemical constituent in the Ashitaba plant is Xanthoangelol which has antioxidant properties. The antioxidant activity of  Xanthoangelol compound is also thought to have the activity of inhibiting the tyrosinase enzyme. In silico test is a method in the development of new drugs. The in silico method provides an evaluation of the potential farmacologyc activities of chemical compound by docking using the Molegro Virtual Docker computer program. The receptor used uses Protein Tyrosinase PDB Code 3NQ1 with KOJ_B_1351 Ligand. Xanthoangelol and Kojic Acid toxicity prediction was carried out using the pkCSM online tool program. Data analysis was performed by comparing the bond energies of the docking results between Xanthoangelol, Kojic Acid, and Ligands at the target receptors. The in silico test results showed that the bond energy of Xanthoangelo was -96.1232 kcal/mol, Kojic Acid -43.6097 kcal/mol, and Ligand KOJ_B_1351 -48.2213 kcal/mol. The in silico test results using the Mollegro program and the pkCSM online tool show that the Xanthoangelol compound has the potential to inhibit the tyrosinase enzyme and has relatively low toxicity, so it can be used as a candidate as a face lightening agent. ABSTRAKEnzim tirosinase berperan penting pada sintesis melanin.yang berperan pada proses hiperpigmentasi kulit., Salah satu kandungan utama Pada tanaman Ashitaba ialah Xanthoangelol yang mempunyai sifat Antioksidan. Aktifitas Antioksidan pada senyawa Xanthoangelol ini diperkirakan juga memiliki aktifitas menginhibisi enzyme tirosinase. Uji in silico merupakan metode dalam pengembangan obat baru. Metode in silico memberikan evaluasi terhadap potensi aktifitas farmakologis suatu senyawa obat dengan melakukan docking menggunakan program komputer Molegro Virtual Docker. Reseptor yang digunakan menggunakan Protein Tirosinase Kode PDB 3NQ1 dengan Ligan KOJ_B_1351. Prediksi toksisitas Xanthoangelol dan Asam Kojic dilakukan menggunakan program pkCSM online tool. Analisis data dilakukan dengan membandingkan energi ikatan hasil docking antara Xanthoangelol, Asam Kojic, dan Ligan pada reseptor target. Hasil uji in silico menunjukkan bahwa energi ikatan Xanthoangelo -96.1232 kkal/mol, Asam Kojic -43.6097 kkal/mol, dan Ligan KOJ_B_1351 -48.2213 kkal/mol. Hasil uji in silico menggunakan program mollegro dan pkCSM online tool menunjukkan bahwa senyawa Xanthoangelol mempunyai potensi untik menginhibisi enzim tirosinase dan memiliki toksisitas yang relatif rendah, sehingga dapat dijadikan kandidat sebagai Bahan pencerah wajah.